Radon Therapy for Autoimmune Diseases Pemphigus and Diabetes: 2 Case Reports - Shuji Kojima; Jerry M. Cuttler; Noriko Shimura; Hironobu Koga; Akihisa Murata; Akira Kawashima (SAGE Publishing, 2019)
We report on the application of radon therapy to relieve the suffering of 2 patients with autoimmune diseases, one with pemphigus with an old myocardial infarction and diabetes mellitus and the other with type I diabetes. We include a lengthy discussion of the biological mechanisms that we believe produced the observed benefits. During the 6 to 9 months of the treatments, the marker values decreased to the upper limit of their normal ranges and the symptoms of the diseases were alleviated. Disorders of Th1/Th2 balance are implicated in the onset of many diseases, including autoimmune diseases. Our decision to give radon ( 222 Rn) therapy to these patients was based on the results of 2 similar case reports and our earlier mouse experiments, which indicated that low doses of radiation induce regulatory T cells. Regulatory T cells regulate the T helper 1 cell and the T helper 2 cell balance. There are more than 80 different autoimmune diseases that are treated with anti-inflammatory agents or immune-suppressing drugs because the exact causes of these diseases and the cures are unknown. These and other case reports indicate that proper radon therapy is an effective treatment. We urge physicians to consider radon as a standard therapy for refractory autoimmune diseases.